Spatial Distributio n of Economic Facilities in Tondo Urban Village, Palu City - Ikbal; Iwan Alim Saputra (Tadulako Science and Technology Journal, 2023)
This research was conducted in Tondo Village, Palu City with the aim of knowing the spatial distribution (distribution and distribution patterns ) of economic facilities in Tondo Village, Palu City, knowing the characteris tics of economic facilities (Shops and Warungs ) in Tondo Village, Palu City. This research is a descriptive survey method research with samples taken using Saturated samples (taken all) for distribution and spatial patterns to determine the characteristics of respondents using simple random sampling, namely 15% of the population of 38 respondents Stores and 23 responses and Warungs from the entire population of 253 Stores and 152 Warungs in Tondo village, data collected through observation, interviews , and document recording methods whose results were analyzed using Nearest neighbor analysis , the results showed that the spatial distribution pattern of Stores and Warungs in Tondo Village showed a clustering pattern. The characteristics of economic facilities (shops and stalls ) in Tondo Village , Palu city are owned by traders with an average age of 30 to 40 years with a high school education level, the income earned from the shop business is Rp.6,293,478, per month and the average shop business income is Rp.9,131,579, per month, the reason for choosing a business location is because they see an opportunity that the enthusiasm of buyers in this location is more promising for profit, the length of time they have been in the shop and shop business is above five years on average